2021
DOI: 10.1002/ddr.21787
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and structure–activity relationship study of O‐prenylated 3‐acetylcoumarins as potent inhibitors of soybean 15‐lipoxygenase

Abstract: In this work, the design, synthesis, and structure-activity relationships of a novel array of geranyloxy and farnesyloxy 3-acetylcoumarins were reported as potent soybean 15-lipoxygenase inhibitors. Among the prepared coumarins, 7-farnesyloxy-3-acetylcoumarin (12b) was found to be the most potent inhibitor by IC 50 = 0.68 μM while O-geranyl substituents at positions 5 and 6 of 3-acetylcoumarin (10a and 11a)were not inhibitors. Using docking studies, the binding affinity and the preferred pose of synthetic comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The main reason is that the water activity of whole wheat flour treated by superheated steam remained at a low level. Zerangnasrabad et al (2021) prepared coumarin to inhibit soybean LOX. The results showed that O ‐prenylated 3‐acetylcoumarins was an effective inhibitor of soybean LOX in the prepared coumarin.…”
Section: Passivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reason is that the water activity of whole wheat flour treated by superheated steam remained at a low level. Zerangnasrabad et al (2021) prepared coumarin to inhibit soybean LOX. The results showed that O ‐prenylated 3‐acetylcoumarins was an effective inhibitor of soybean LOX in the prepared coumarin.…”
Section: Passivationmentioning
confidence: 99%
“…In addition, the LOX activity of whole wheat flour treated by superheated steam showed a downward trend in the later storage process. The main reason is that the water activity of whole wheat flour treated by superheated steam remained at a low level Zerangnasrabad et al (2021). prepared coumarin to inhibit soybean LOX.…”
mentioning
confidence: 99%
“…Up until now, methods for the preparation of selenophenols have commonlybeen based on harsh chemical processes such as Grignard chemistry [ 15 ], nucleophilic-aromatic-type substitutions [ 16 ], or Sandmeyer-type chemistry [ 17 ]. The Newman-Kwart rearrangement is an effective and valid reaction in which the aryl group of an O -aryl thiocarbamate, ArOC(=S)NMe 2 , migrates from the oxygen atom to the sulfur atom, forming an S -aryl thiocarbamate, ArSC(=O)NMe 2 [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…They are nonheme iron-containing proteins that contribute to a new eicosanoid pathway by acting as biocatalysts in arachidonic acid’s peroxidation at positions 5, 8, 12, and 15 to the corresponding hydroperoxide derivatives. In this context, Seyedi and co-workers reported a novel array of geranyloxy and farnesyloxy 3-acetylcoumarins as potent soybean 15-lipoxygenase inhibitors ( Zerangnasrabad et al, 2021 ). 7-Farnesyloxy-3-acetylcoumarin ( 201 ) was found to be the best inhibitor with an IC 50 value of 0.68 µM (reference 4-MMPB, IC 50 = 18 µM) ( Figure 4 ).…”
Section: Biological Applications Of Coumarin Derivativesmentioning
confidence: 99%